1990
DOI: 10.1021/bi00480a002
|View full text |Cite
|
Sign up to set email alerts
|

Importance of minor-groove contacts for the recognition of DNA by the binding domain of Hin recombinase

Abstract: Incorporation of the DNA-cleaving moiety EDTA.Fe at discrete amino acid residues along a DNA-binding protein allows the positions of these residues relative to DNA bases, and hence the organization of the folded protein, to be mapped by high-resolution gel electrophoresis. A 52-residue protein, based on the sequence-specific DNA-binding domain of Hin recombinase (139-190), with EDTA at the NH2 terminus cleaves DNA at Hin recombination sites. The cleavage data for EDTA-Hin(139-190) reveal that the NH2 terminus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 47 publications
(70 reference statements)
3
28
0
Order By: Relevance
“…4D and 6A) showed that methylation of residues in either the major or minor groove inhibited AbaA binding, supporting the conclusion that the protein makes essential contacts in both grooves. Only a few other proteins make essential contacts in both grooves (4,40,46). Furthermore, this observation is consistent with the proposed interactions between 3-sheets and the minor groove of DNA (16 (52).…”
Section: '-G G T C C a T G T A A G G T T A G T T G T T A C G T T C Tsupporting
confidence: 83%
“…4D and 6A) showed that methylation of residues in either the major or minor groove inhibited AbaA binding, supporting the conclusion that the protein makes essential contacts in both grooves. Only a few other proteins make essential contacts in both grooves (4,40,46). Furthermore, this observation is consistent with the proposed interactions between 3-sheets and the minor groove of DNA (16 (52).…”
Section: '-G G T C C a T G T A A G G T T A G T T G T T A C G T T C Tsupporting
confidence: 83%
“…1A). The interactions between the minor groove of substrate DNA and the γδ resolvase arm region residues Arg 125, Thr 126, Gly 129, Arg 130, Phe 140, Gly 141, and Arg 142 provide the structural and functional foundation for DNA association (31,32). Comparative sequence analysis of functionally divergent resolvases and invertases and their cognate DNA binding sites suggests that variable arm region positions may also provide the basis for catalytic domain sequence specificity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that a synthetic peptide ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 24, 1235-1247 consisting of residues 139-190 (52-amino-acid peptide) of Hin bound specifically to a hix half-site (Sluka et al, 1990). The difference between the binding affinity of the 52-amino-acid peptide (K d Ϸ10 ¹7 ) and the wild-type Hin dimer (K d Ϸ10 ¹9 ) was partly attributed to the co-operative interactions between the amino-terminal domains required for dimer formation (Bruist et al, 1987b;Sluka et al, 1987;Glasgow et al, 1989a).…”
Section: Discussionmentioning
confidence: 99%
“…A C-terminal 52-amino-acid polypeptide of Hin recombinase (residues 139-190) has been shown to contain the DNA-binding domain (Sluka et al, 1987). Biochemical and crystallographic data have demonstrated that a helix-turn-helix structure (residues 149 to 180) makes specific contacts in the major groove with nucleotides at positions 9 and 10 of the hix half-site (Glasgow et al, 1989a;Sluka et al, 1990;Hughes et al, 1992;Feng et al, 1994b) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%